The Characterization of Fuzzy and Anti Fuzzy Ideals in AG-groupoid - Kausar, Nasreen; Munir, Muhammad; Agarwal, Praveen; Kalaiarasi, Kalaichelvan (CHIANG MAI UNIV, FAC SCIENCE, 2022)
Fuzzy and anti fuzzy ideals in ordered AG-groupoid are the modern tool for handling uncertainty in many decisions making problems. The purpose of this paper is to investigate, the characterizations of different classes of non-associative ordered semigroups by using anti fuzzy left (resp. right) interior, weakly regular, (2, 2)-regular ideals. The algebraic properties of ideals in AG-groupoid are examined for the newly introduced fuzzy algebra. The results presented are justified by providing examples of well-defined and well-established AG-groupoid.
Keywords: Fuzzy sets; anti fuzzy AG-subgroupoids; anti fuzzy left (resp. right) interior ideals; left (resp. right) weakly; intra-(2, 2) regular ordered AG-groupoids; Mathematics